Integration of productive waqf in Sharia insurance: Enhancing investment and life protection - Ahyani, Hisam; Solehudin, Ending; Mutmainah, Naeli; Adnan, Nurul Ilyana Muhd (Review of Islamic Social Finance and Entrepreneurship, 2024)
Purpose – This study investigates the integration of productive waqf into Sharia insurance in Indonesia and its contribution to investment benefits and life protection. It aims to explore how waqf can enhance the economic and social impacts of Sharia insurance products.Methodology – A qualitative approach was employed, involving a comprehensive review of the literature on waqf, Sharia insurance, and Islamic finance. Additionally, interviews were conducted with experts in Sharia insurance and waqf management to gather insights into the current practices and challenges.Findings – This study reveals that productive waqf initiatives within Sharia insurance have the potential to significantly improve investment returns and expand the scope of life protection benefits offered to participants. It identifies key areas in which waqf funds can be deployed effectively, such as long-term investment projects and social welfare programs.Implications – The findings have practical implications for policymakers, Sharia insurance providers, and waqf administrators in enhancing collaboration to maximize the socio-economic benefits of waqf. By integrating waqf into insurance products, stakeholders can foster sustainable development and financial inclusivity.Originality – This study contributes to the literature by offering insights into the innovative use of waqf within the dynamic context of Sharia insurance. It underscores the originality of leveraging waqf assets to address contemporary socioeconomic challenges and promote ethical finance principles.